An Investigation on Eco Friendly Self-Compacting Concrete Using Spent Catalyst and Development of Structural Elements - Balamuralikrishnan R.; Ranya Al-Balushi; Asima Kaleem (Salehan Institute of Higher Education, 2023)
The theme of this initiative is